2022
DOI: 10.3390/cells11192995
|View full text |Cite
|
Sign up to set email alerts
|

MgrB Mutations and Altered Cell Permeability in Colistin Resistance in Klebsiella pneumoniae

Abstract: There has been a resurgence in the clinical use of polymyxin antibiotics such as colistin due to the limited treatment options for infections caused by carbapenem-resistant Enterobacterales (CRE). However, this last-resort antibiotic is currently confronted with challenges which include the emergence of chromosomal and plasmid-borne colistin resistance. Colistin resistance in Klebsiella pneumoniae is commonly caused by the mutations in the chromosomal gene mgrB. MgrB spans the inner membrane and negatively reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…For example, activation of a PhoPQ two-component system results in increased mgrB transcription, which then negatively suppresses the phosphorylation of PhoP. Mutations in mgrB prevent this negative feedback suppression of phosphorylation of PhoP, and, as a result, can alter colistin susceptibility [ 10 ]. Furthermore, efflux pump overexpression, porin loss and upregulation of capsular biosynthesis all have a role in colistin susceptibility [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, activation of a PhoPQ two-component system results in increased mgrB transcription, which then negatively suppresses the phosphorylation of PhoP. Mutations in mgrB prevent this negative feedback suppression of phosphorylation of PhoP, and, as a result, can alter colistin susceptibility [ 10 ]. Furthermore, efflux pump overexpression, porin loss and upregulation of capsular biosynthesis all have a role in colistin susceptibility [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The work of Timothy J and co-workers demonstrated that mgrB mutation induces PhoPQ-governed lipid A remodeling, which not only confers not only resistance to polymyxins but also enhances K. pneumoniae virulence by decreasing antimicrobial peptide susceptibility and attenuating early host defense response activation. 44,45 Resistance to colistin and polymyxin B is associated with lipid A remodeling. In this study, lipid A was also extracted from the RA-LZ01 and RA-LZ01ΔRaEptA using a method for isolation of lipid A F I G U R E 4 MALDI-TOF mass spectrometry determination of altered structures of LPS-lipid A anchored on the bacterial surface upon the expression of RaEptA and its 5-point mutants.…”
Section: Discussionmentioning
confidence: 99%
“…This may demonstrate a divergent scenario whereby an AMR mechanism helps to enhance virulence. The work of Timothy J and co‐workers demonstrated that mgrB mutation induces PhoPQ‐governed lipid A remodeling, which not only confers not only resistance to polymyxins but also enhances K. pneumoniae virulence by decreasing antimicrobial peptide susceptibility and attenuating early host defense response activation 44,45 . Resistance to colistin and polymyxin B is associated with lipid A remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…The mgrB gene, a small transmembrane protein with 47 amino acids spanning the inner membrane, plays a role in negatively regulating PhoP phosphorylation-a process vital for bacterial outer membrane lipid biosynthesis. (29,30) Recent studies have demonstrated that nonmcr-associated CLR is frequently linked to alterations in the mgrB gene, as well as variations in the crrB, pmrB, phoQ, pmrA, and phoP genes. (29,30) Isolates carrying mcr genes exhibited resistance to colistin by the microdilution test (MIC ≤ 4 mg/L), and remarkably, all of these isolates displayed identical PFGE patterns, indicating their origin from a single clone.…”
Section: Discussionmentioning
confidence: 99%
“…(29,30) Recent studies have demonstrated that nonmcr-associated CLR is frequently linked to alterations in the mgrB gene, as well as variations in the crrB, pmrB, phoQ, pmrA, and phoP genes. (29,30) Isolates carrying mcr genes exhibited resistance to colistin by the microdilution test (MIC ≤ 4 mg/L), and remarkably, all of these isolates displayed identical PFGE patterns, indicating their origin from a single clone. Similar data were observed in Jordan, where out of 179 CRKP isolates, only one carried the mcr-1 gene, and the prevalence was 1.1%.…”
Section: Discussionmentioning
confidence: 99%